Approaches to detect the drug resistance in acute leukemia - Funato, Tadao; Takeda, Mayu (Journal of Electrophoresis, 2005)
Resistance to chemotherapy is an obstacle to the successful treatment of acute myeloid leukemia (AML). Failure of therapeutic treatment may be due to the development of multidrug resistance (MDR), the mechanisms of which include upregulation of membrane-resident transporters which efflux chemotherapeutic drugs from tumor cells, as well as failure of cancer cells to undergo apoptosis in response to chemotherapy. We developed a quantitative reverse transcription PCR method for MDR1 and multidrug resistance-related protein 1 (MRP1) transcripts to evaluate drug resistance, and applied it to clinical samples. P-glycoprotein encoding MDR1 (P-gp) expression was determined by Western blot analysis, rhodamine 123 was used for functional study of P-gp protein, and sensitization of leukemic cells to drugs was quantified by methyl thiazolyl tetrazolium (MTT) assays. In this review, we cover current findings and suggest that the different methods for determining MDR and, in particular, discuss the efficacy of this quantitative analysis of MDR1 transcripts for the prediction of clinical drug resistance in acute leukemia.